Subgenome-biased expression and functional diversification of a Na+/H+ antiporter homoeologs in salt tolerance of polyploid wheat - Zheng, Mei; Li, Jinpeng; Zeng, Chaowu; Liu, Xingbei; Chu, Wei; Lin, Jingchen; Wang, Fengzhi; Wang, Weiwei; Guo, Weilong; Xin, Mingming; Yao, Yingyin; Peng, Huiru; et al. (Frontiers in Plant Science, 2022)
Common wheat (Triticum aestivum, BBAADD) is an allohexaploid species combines the D genome from Ae. tauschii and with the AB genomes from tetraploid wheat (Triticum turgidum). Compared with tetraploid wheat, hexaploid wheat has wide-ranging adaptability to environmental adversity such as salt stress. However, little is known about the molecular basis underlying this trait. The plasma membrane Na+/H+ transporter Salt Overly Sensitive 1 (SOS1) is a key determinant of salt tolerance in plants. Here we show that the upregulation of TaSOS1 expression is positively correlated with salt tolerance variation in polyploid wheat. Furthermore, both transcriptional analysis and GUS staining on transgenic plants indicated TaSOS1-A and TaSOS1-B exhibited higher basal expression in roots and leaves in normal conditions and further up-regulated under salt stress; while TaSOS1-D showed markedly lower expression in roots and leaves under normal conditions, but significant up-regulated in roots but not leaves under salt stress. Moreover, transgenic studies in Arabidopsis demonstrate that three TaSOS1 homoeologs display different contribution to salt tolerance and TaSOS1-D plays the prominent role in salt stress. Our findings provide insights into the subgenomic homoeologs variation potential to broad adaptability of natural polyploidy wheat, which might effective for genetic improvement of salinity tolerance in wheat and other crops.